HOW IS SOCIAL MEDIA GATEKEEPING DIFFERENT? A MULTI- PLATFORM COMPARATIVE ANALYSIS OF THE NEW YORK TIMES - Andringa, Peter; Duquette, David; Dwyer, Deborah; Napoli, Philip; Ronald, Petra (AoIR Selected Papers of Internet Research, 2018)
News audiences are increasingly fragmented across different media platforms. Consequently, individual news organizations simultaneously disseminate their content across different media. Each of these media has different user bases, interface characteristics, and distribution systems. Given these substantial differences, the dynamics of the gatekeeping process – and the news values that guide this process – vary across different media technologies/platforms. As audience attention migrates from older to newer platforms (such as social media), it is increasingly important that we understand how the nature of the news that is disseminated – and thus consumed – may be different from the news disseminated through more traditional means. The ramifications of these differences can be profound if the news disseminated on the newer platforms is, for example, more or less substantive, more or less diverse, or more or less plentiful than the news disseminated on older technologies/platforms. This study addresses these issues through a comparative gatekeeping analysis of the New York Times. For this study, a month’s worth of New York Times front page, home page, and Facebook page story output are comparatively analyzed across dimensions such as story quantity, story duplication, hard versus soft news, and content diversity. The primary goal is to determine if or how the nature of the news that is prioritized for news consumers differs between the social media context and older contexts such as the print front page and the web home page.